Rancang bangun unit pengolahan air limbah industri Penyamakan kulit ikan pari di labuan maringgai, Lampung timur - Sunaryo, Ignatius; Sutyasmi, Sri (Majalah Kulit, Karet, dan Plastik, 2007)
This waste water treatment plant (WWTP) was designed and built to treat the waste water coming from the sting rays leather tannery in Labuan Maringgai, Lampung Selatan. By treating this kind of waste water coming from the sting rays leather tannery, it will decrease the environmental pollution. The product capacity of this tannery was 400 pieces per month and the weight of it was 120 kg. Those skins were tanned into two steps, the number of skins in each process was 200 pieces or 60 kg during 2 weeks. The volume of waste water discharged variedÂ  from 1,5 to 5 m3 during 3 days in the beginning of beam house operation or 0.5 to 1 m3per day during the first step of process. The pollution content of such waste water was as follows: COD: 1205,66 -Â  1400 mg/l; BOD 550 â 950 mg/l; S : 28,9 â 213 mg/l, TSS: 55,16 â 775 mg/l; N-NH3 : 30,18 â 129,6 mg/l; fat/oil : 21 â 292. mg/l; total Cr: 0,47 â 0,76 mg/l; and pH: 9 â 12 respectively. The work hours in operating the WWTP was 5 hours per day, and the debit of it ranged from 0.5 to 1 m3 per hour. The WWTP was designed for the max COD of 1.500 mg/l and BOD 750 mg/l. The system of WWTP was pre treatment, homogenization, flocculation and coagulation, 1stÂ  anaerobic facultative and 2nd anaerobic facultative, sludge drying bed and final control tank. The efficiency of this WWTP ranged from 22,53 to 97%.Â Key word: stin rays, leather tanning, waste water, plant design, wwtp, environmentÂ  Â ABSTRAKÂ Unit pengolahan air limbah (UPAL) ini dirancang dan dibangun untuk mengolah air limbah dari pabrik penyamakan kulit ikan pri di Labuan Maringgai, Lampung Timur. Dengan terolahnya air limbah dari pabrik tersebut, berarti akan menurunkan tingkat pencemaran ke lingkungan. Kapasitas produksi pabrik tersebut per bulan adalah sebesar 400 lebmar, dengan berat 120 kg. Kulit sebanyak itu diproses 2 sekali @ 200 lembar atau 60 kg, dan akan menghasilkan air limbah sekitar 1,5 â 5 m3 per hari, dengan kandungan COD: 1205,66 â 1400 mg/l; BOD 550 â 950 mg/l; S : 28,9 â 213 mg/l, TSS: 55,16 â 775 mg/l; N-NH3 : 30,18 â 129,6 mg/l; lemak : 21 â 292. mg/l; total Cr: 0,47 â 0,76 mg/l; danÂ  pH: 9 â 12. UPAL tersebut diopersikan selama 5 jam/hari dengan debit berkisar antara 0,5 sampai 1 m3 per jam, dengan tingkat pencemaran COD 1.500 mg/l dan BOD maks 750 mg/l. Unit pengolahan air limbah (UPAL) ini terdiri dari perlakuan awal pre treatment (penyaringan pengendapan awal), penampungan (homogenisasi), perlakuan kimia (flokulasi/koagulasi), fakultatif anaerob I, fakultatif anaerob II, penyaringan lumpur dan bak kontrol akhir. Efisiensi pengolahan berkisar antara 22,53 sampai 97%.Â Kata kunci: air limbah, rancang bangun, UPAL, lingkungan.